Isotocin Regulates Growth Hormone but Not Prolactin Release From the Pituitary of Ricefield Eels - Yang, Wei; Zhang, Ning; Shi, Boyang; Zhang, Shen; Zhang, Lihong; Zhang, Weimin (Frontiers in Endocrinology, 2018)
The neurohypophyseal hormone oxytocin (Oxt) has been shown to stimulate prolactin (Prl) synthesis and release from the adenohypophysis in rats. However, little is known about the functional roles of Oxt-like neuropeptides in the adenohypophysis of nonmammalian vertebrates. In the present study, cDNAs encoding ricefied eel oxytocin-like receptors (Oxtlr), namely isotocin (Ist) receptor 1 (Istr1) and 2 (Istr2), were isolated and specific antisera were generated, respectively. RT-PCR and Western blot analysis detected the presence of both Istr1 and Istr2 in the brain and pituitary but differential expression in some peripheral tissues including the liver and kidney, where only Istr1 was detected. In the pituitary, immunoreactive Istr1 and Istr2 were differentially distributed, with the former mainly in adenohypophyseal cell layers adjacent to the neurohypophysis whereas the latter in peripheral areas of the adenohypophysis. Double immunofluorescent images showed that immunostaining of Istr1 but not Istr2 was localized to growth hormone (Gh) cells, but neither of them was expressed in Prl cells. Ist inhibited Gh release in primary pituitary cells of ricefield eels and increased Gh contents in the pituitary gland of ricefield eels at 6 hrs after in vivo administration. Ist inhibition of Gh release is probably mediated by cAMP, PKC/DAG, and IP3/Ca2+ pathways. In contrast, Ist did not affect either prl gene expression or Prl contents in primary pituitary cells. Results of the present study demonstrated that Ist may not be involved in the regulation of Prl but inhibit Gh release via Istr1 rather than Istr2 in ricefield eels, and provided evidence for the direct regulation of Gh cells by oxytocin-like neuropeptides in the pituitary of non-mammalian vertebrates.